2007
DOI: 10.1177/1045389x07076277
|View full text |Cite
|
Sign up to set email alerts
|

Active Vibration Control Strategy for a Single-Link Flexible Manipulator Using Ionic Polymer Metal Composite

Abstract: Ionic polymer metal composites (IPMC) are a class of electro-active polymers (EAP) that produce mechanical strain in response to electrical stimulation and vice versa. The property of generating high strains with low actuation voltage makes IPMC suitable for mechanical actuators in applications involving control of high-amplitude vibration. This article describes results on an application of IPMC as an active damper for large deflection vibration control of a single link rotating flexible manipulator. Modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Newbury and Leo reported that response of IPMCs is initial condition dependent including pre-imposed/initial curvature [37]. Radius of curvature ρ can be approximately determined at a given tip displacement s (6) and (b) Equivalent coupling coefficient b d 31 by equation (7) where κ and L are the curvature and length of the strip, respectively [38]. For the case of initial curvature, s 0 is the initial tip displacement prior to actuation.…”
Section: Finite Element Simulations Of Curved Ipmc Actuators-effect Omentioning
confidence: 99%
“…Newbury and Leo reported that response of IPMCs is initial condition dependent including pre-imposed/initial curvature [37]. Radius of curvature ρ can be approximately determined at a given tip displacement s (6) and (b) Equivalent coupling coefficient b d 31 by equation (7) where κ and L are the curvature and length of the strip, respectively [38]. For the case of initial curvature, s 0 is the initial tip displacement prior to actuation.…”
Section: Finite Element Simulations Of Curved Ipmc Actuators-effect Omentioning
confidence: 99%
“…The details of the controller design are discussed in Ref. [21]. Sensor data is collected by PC interfaced DAQ-PCI-6251 and NI-DAQmx (supplied by National Instrumentation) with signal conditioner.…”
Section: Methodsmentioning
confidence: 99%
“…Two patches of IPMC are used to actively damp the vibration of flexible link. A distributed active strain is generated by driving the required voltage through the IPMC when it is used as active damper [21][22]. Figure 6 shows both the undamped and damped response of the flexible link for square torque input.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Active vibration and noise control of distributed parameter flexible systems with delay were also investigated. 23,24…”
Section: Introductionmentioning
confidence: 99%